Prevalence of upper extremity pain in a population of people with paraplegia. Issue 7 (July 2018) - Kentar, Y.; Zastrow, R.; Bradley, H.; Brunner, M.; Pepke, W.; Bruckner, T.; Raiss, P.; Hug, A.; Almansour, H.; Akbar, M.
Abstract Study design Cross-sectional study. Objectives To determine the prevalence, patterns, and predictors of musculoskeletal pain in the upper extremity joints among wheelchair-dependent individuals with post-traumatic paraplegia. Secondarily, to document most common reported causes of upper extremity pain. Setting Centre for Orthopaedics, Trauma Surgery and Spinal Cord Injury, Germany. Methods The study was done by means of a structured questionnaire, which was mailed to the individuals who had been treated between 1990 and 2007 for newly sustained or pre-existing, accident-related paraplegia (n = 670). The questionnaire was designed mainly to obtain the information regarding shoulder, elbow, and wrist pain. Additional data included participant demographics, mechanism, level and completeness of injury as well as wheelchair dependence and time since injury. The Frankel classification system was used to define the completeness of injury. Results Four hundred and fifty-one (67%) questionnaires were included. Pain was reported by approximately 81% of the participants. Of this sample, 61% had shoulder pain, 33% had elbow pain, and 43% had wrist pain, 19% had shoulder, elbow, and wrist pain, 27% had shoulder and elbow pain, 34% had shoulder and wrist pain, 21% had elbow and wrist pain. The main diagnoses were rotator cuff tears for individuals with shoulder pain, epicondylitis for those with elbow pain, and carpal tunnel syndrome for those with wrist pain. The development of shoulder/elbow and wrist pain correlated with age and time since injury. Conclusions Age and the length of time since injury correlated with a higher rate of shoulder, elbow, and wrist pain. The completeness of injury, neurological level, and gender were correlated with shoulder, elbow, and wrist pain, respectively.